Comorbidity of dispressive and dermatologic disorders : therapeutic aspects - Filaković, Pavo (Array, 2009)
Depressive disorders are more common in the population affected with dermatologic disorders. In depression and dermatology disorders in which certain precipitating factors are required thereby causing alteration of the patient's immunological identity causing a combination of hereditary features and ones acquired through adaptation occur to cause the disorder to develop. Treatment of depressive and dermatologic disorders is complex and requires an integral therapeutic approach encompassing all aspects of both disorders and their comorbidity.